Piezoelectric effect and spontaneous polarization in computer modelling of AIII–N heterostructures - Piasecki, Tomasz; Kośnikowski, Wojciech; Paszkiewicz, Bogdan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The Ga, Al and In nitrides (AIII–N) are complete material system suitable in high power and high temperature electronic devices such as AlxGa1–xN/GaN heterostructure field effect transistor (HFET). The examples of computer modelling of AIII–N heterostructures were shown. AIII–N materials exhibit strong piezoelectric and spontaneous polarization. The computer modelling results showing the influence of layer polarity on carrier distribution in AlxGa1–xN/GaN heterostructure were shown. Only in Ga-faced heterostructures 2-dimensional electron gas (2DEG) is formed. The effect of AlxGa1–xN layer relaxation on 2DEG concentration in AlxGa1–xN/GaN heterostructure was examined. The difference in spontaneous polarization in AlxGa1–xN and GaN caused high 2DEG concentration even in AlxGa1–xN/GaN heterostructures with relaxed AlxGa1–xN layer. Polarization field in AlxGa1–xN layer in AlxGa1–xN/GaN heterostructure was enough for achieving high 2DEG concentrations in undoped heterostructure. Strained AlxGa1–xN layer was introduced into typical HFET heterostructure. GaN layer above an interlayer was depleted and the negative influence of using non semi-insulating GaN layer in HFET transistor was reduced.
Optica Applicata, Vol. 35, 2005, nr 3, s. 597-604
Keywords: optyka; AIII–N; computer modelling; heterostructure; 2-dimensional electron gas (2DEG); strain; piezoelectric effect; spontaneous polarization; heterostructure field effect transistor (HFET)